2022
DOI: 10.1093/sleep/zsac156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of psychometric properties of patient-reported outcome measures frequently used in narcolepsy randomized controlled trials: a systematic review

Abstract: Study objectives To systematically determine subjective and objective outcome measures used to measure efficacy of narcolepsy interventions in randomized controlled trials (RCTs) in adults and children and assess psychometric properties of patient-reported outcome measures (PROMs) used. Methods We searched bibliographical databases and clinical trial registries for narcolepsy RCTs and extracted objective and subjective outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Over a decade later, the situation remains essentially unchanged. In a review of 80 outcome measures used for 100 randomized controlled trials in narcolepsy interventions, authors found ‘surprisingly little evidence for the validity, reliability, and responsiveness of [the instrument] frequently used to assess treatment efficacy in narcolepsy’ ( Schokman et al, 2022 ). Unfortunately, this pattern is repeated in various disciplines, across different populations and diagnostic categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over a decade later, the situation remains essentially unchanged. In a review of 80 outcome measures used for 100 randomized controlled trials in narcolepsy interventions, authors found ‘surprisingly little evidence for the validity, reliability, and responsiveness of [the instrument] frequently used to assess treatment efficacy in narcolepsy’ ( Schokman et al, 2022 ). Unfortunately, this pattern is repeated in various disciplines, across different populations and diagnostic categories.…”
Section: Discussionmentioning
confidence: 99%
“…The dearth of quality instruments in healthcare clearly indicates to the clinicians, educators, and researchers that it is in the patients’ and health professionals’ best interests to engage with psychometrics and upskill in knowledge in the field. Too often, instruments are developed poorly, leading to all subsequent data and treatment findings based on their data being questionable ( Schokman et al, 2022 ). Instrument development is a dynamic, iterative process involving creativity, theory, statistical evaluation, and dedication from the instrument authors.…”
Section: Discussionmentioning
confidence: 99%
“…There is an imperative need to use instruments that have been validated to increase the likelihood that they accurately measure what they are intended to measure (Waschl and Chen, 2022; Ladak et al , 2022). A suitable measurement is one that is supported by published evidence indicating patient acceptability, reliability, validity and responsiveness (Kowalchuk Horn et al , 2012; Schokman et al , 2022).…”
Section: Introductionmentioning
confidence: 99%